Functional overreaching: The key to peak performance during taper - Aubry, A.; Le Meur, Y.; Hausswirth, C.; Maze, B.; Bignet, F. (2015)
Vortrag des Referenten auf der Science + Triathlon 2015 World Conference vom 26.-27. November 2015 am INSEP in Paris